Do recalcitrant seeds really exist? - Claudio José Barbedo; Danilo da Cruz Centeno; Rita de Cássia Leone Figueiredo Ribeiro (Hoehnea)
In the 70's, seeds were divided into two categories: recalcitrant and orthodox. In the 80's, it was necessary to create an intermediate category; from the 90's onwards, a gradient between orthodox and recalcitrant categories has been considered by several authors. Currently, the terms orthodox and recalcitrant are appropriate just for technological purposes, not for scientific studies. It seems that the differences between recalcitrant and orthodox seeds lie only on the maturity stage in which they are detached from the mother plant, the recalcitrant ones in a very immature stage. This implies that little progress should be expected to expand the storability of these recalcitrant seeds with the application of any treatment after harvesting. Efforts shall be focused on amplifying the maturation period of these seeds by keeping them linked to the mother plant until the maturation process has been completed.